2016
DOI: 10.1002/cctc.201600247
|View full text |Cite
|
Sign up to set email alerts
|

Meldrum's Acid: A Useful Platform in Asymmetric Organocatalysis

Abstract: For more than a hundred years, Meldrum's acid and its derivatives have proven their utility and versatility in organic synthesis. Showing very unusual properties and multiple facets of reactivity, this small architecture has become the keystone of numerous synthetic methodologies. In asymmetric organocatalysis, where the catalyst/substrate matching is of upmost importance, Meldrum's acid derivatives have slowly but surely emerged as partners of choice over the last decade. This review intends to give a compreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…[11][12][13] We recently reported as traightforward elaboration of a-substituted isoxazolidinones 3, [14] from readily available C5-substituted Meldrum's acids 1 and a-sulfonyl amide 2 (Scheme1b). [15,16] This sequencen ot only complements the few synthetic approachest oa-substitutedi soxazolidin-5-ones of type 3 describedi nt he literature (NHo rNBn derivatives), [13] but affords uniquep recursors of N-Boc protected b 2 -AA. [13b, 14] The construction of 3 is basedo na ni nnovative domino (3 + 2)-annulation-decarboxylation reactiont erminated by the protonation of the potassium enolate 4a.A ctually,a na symmetricv ersion was achieved by meansofachiral Brønsted base.…”
mentioning
confidence: 89%
“…[11][12][13] We recently reported as traightforward elaboration of a-substituted isoxazolidinones 3, [14] from readily available C5-substituted Meldrum's acids 1 and a-sulfonyl amide 2 (Scheme1b). [15,16] This sequencen ot only complements the few synthetic approachest oa-substitutedi soxazolidin-5-ones of type 3 describedi nt he literature (NHo rNBn derivatives), [13] but affords uniquep recursors of N-Boc protected b 2 -AA. [13b, 14] The construction of 3 is basedo na ni nnovative domino (3 + 2)-annulation-decarboxylation reactiont erminated by the protonation of the potassium enolate 4a.A ctually,a na symmetricv ersion was achieved by meansofachiral Brønsted base.…”
mentioning
confidence: 89%
“…[1] Since the seminali nvestigations of Huisgen,[2] ag reat deal of research has been performed not only to extend the scope of these useful annulation processes but also to ascertain whether the exact mechanism of action is based on concerted or nonconcerted events. [4] This novel methodology highlighted 1) the practical use of Meldrum's acid derivatives 1 as a ketene equivalent or C2 synthon; [5] 2) af acile addition reaction of rather acidic Meldrum's acid derivatives 1 (pK a = 4.93 in water for R 1 = H) to nitrones 2 under organocatalytic Brønsted base (R 3 N) conditions despite the poor nucleophilic nature of anion intermediate 4 (step I); [6, 5c] and 3) ad omino reaction likely encompassing af ormal (3 + 2) annulation-fragmentation-decarboxylation-protonations equence towards the formation of product 3 (steps I-III). [4] This novel methodology highlighted 1) the practical use of Meldrum's acid derivatives 1 as a ketene equivalent or C2 synthon; [5] 2) af acile addition reaction of rather acidic Meldrum's acid derivatives 1 (pK a = 4.93 in water for R 1 = H) to nitrones 2 under organocatalytic Brønsted base (R 3 N) conditions despite the poor nucleophilic nature of anion intermediate 4 (step I); [6, 5c] and 3) ad omino reaction likely encompassing af ormal (3 + 2) annulation-fragmentation-decarboxylation-protonations equence towards the formation of product 3 (steps I-III).…”
Section: Introductionmentioning
confidence: 99%
“…Although several teams ventured into this convenient enantioselective protonation (EP) strategy, mostly from hemimalonic esters in organocatalysis, only the groups of Brunner, Rouden, Zhang and Song succeeded in getting good er (rarely > 95:5) albeit at the expense of the use of high catalyst loading (up to 1 equiv.). [11] We reasoned that a novel and readily available MA platform 1 (Scheme 2), [12] may undergo the intramolecular nucleophilic addition of the phenol moiety thanks to the electrophilic character of the carbonyl groups. Context of the investigation.…”
mentioning
confidence: 99%
“…However, the non-asymmetric decarboxylative-cyclization final steps required a heating step (APTS, toluene, 100 8C). [12] Eventually, it was shown that neither the intermolecular addition of phenol nor the direct addition event of catalyst 3 g occurred (Scheme 3b). Proof of principle.…”
mentioning
confidence: 99%
See 1 more Smart Citation